A Capital City at the Margins: Quezon City and Urbanization in the Twentieth-Century Philippines - Pante, Michael D (Archīum Ateneo, 2019)
Quezon City served as the Philippines's capital for almost three decades (1948-1976); yet Filipinos today barely remember this historical fact. Was the city; therefore; a failure? This book answers this question by presenting an unconventional historical geography of twentieth-century Quezon City; one that focuses not on its grandiose architecture and master plan but on its boundaries; peripheries; and marginal areas. In so doing; it shows how the city functioned as a buffer zone mediating between city and countryside; and thus developed due to the urban-rural overlaps inherent in sociohistorical forces such as colonialism; revolution; agrarian unrest; decolonization; migration; and authoritarianism. Not quite Manila-centric; this book is twentieth-century Philippine history from an off-center point of view.